RHB Bank (Singapore) Dancing with the Giants - Lee, Andrian Chong Chee (2013)
This management project attempts to study on RHB Bank Singapore where it is a regional expansion of RHB Banking Group listed in Malaysia. Singapore has been a financial hub for many foreign banks and also operated by three major local banks. With such an intense operation in a small island and filled with so many foreign financial institutions who have loaded with more capital and global experience. This has lead to the study on how RHB Bank in Singapore can compete and should compete with all the big financial institutions operated by foreign banks and local Singapore banks. With this, the theme of this management project is called “RHB Bank Singapore Dancing with the Giants”. This idea on “Dancing with the Giants” is borrowed from the interesting publication by World Bank on Dancing with Giants-China, India and The Global Economy (Yusuf, 2007. In this project paper, three main streams of literature will be used for study and also to assimilate with circumstances from the actual environment. The first literature is adopted from a journal written by Michael Porters in Business Harvard Review in 2008 on the five competitive forces that shape the strategy. This journal shows how to conduct a scanning of the external environment and how the five forces would defines the industry’s structure and ultimately shapes the nature of competitive environment. The second literature is written by Jay Barney (1991) on the firm resources. This is an inward looking model on the organisation itself. It focuses on the use of the organisation’s internal resources and how to create a sustainable competitive advantage. This study uses the VRIO framework that linked between the firm’s resources and how they can create a sustained competitive advantage. VRIO is an acronym referring to the internal resources that are Valuable, Rarity, Imitability and Organisation. The final literature review is extracted from the journal written by Anil Gupta (Apr 2000) on regional strategies. This paper covers on how an organisation manages its regional expansion. It also provides a conceptual framework for analysing the different aspect of operating regionally or to globalise the business. The overall research method will be based on interview. The reason for this approach is due to the fact that information required is mainly internal to RHB Banking Group and most of the information will not be available publically. As such, an interview session with management of RHB would help to provide some insight to their views. Based on the three chosen literature, the reviews provide a framework to analyse how organisation can look at internal resources and thus creating a sustaining competitive advantage. The external forces from Porter would provide a framework on forces that would impact the organisation while carving out their business strategy. Lastly with the regional expansion strategy will show how organisation in Head office strategized with the regional offices to create synergy and thus increasing the shareholders’ value. Only through a sustaining competition, an organisation can have a longer term of survival in the market. All these analysis and findings will help to affirm the strategy adopted based on literature review and also possibly suggest a possible alternative for RHB Singapore to compete with so many local and foreign financial institutions surrounding them in Singapore.